Executing Strategy for Business Results - Authors (Harvard Business Press, 2007)
To survive and thrive under today's competitive conditions, companies must constantly formulate effective strategies - and they must execute those strategies flawlessly. Thankfully, mastering the skills needed to define and carry out strategy is possible. And this volume will help you. Learn about the common pitfalls of strategy creation as well as the tools to successfully surmount the challenges.